Key Influences on Warehouse Rental Prices: A Systematic Review of The Literature - Triono, Heru; Suwarsinah, Heny Kuswanti; Asikin, Zenal (Business Review and Case Studies, 2025)
Background: Warehouse rental costs are a critical component of supply chain management; however, existing studies often focus on isolated factors, such as location or building characteristics. A comprehensive understanding of the interaction between economic conditions, infrastructure, and emerging trends, such as automation and sustainability, remains limited. This study addresses this gap by systematically analyzing the key determinants influencing warehouse rental pricing. Purpose: This study examines the primary factors affecting warehouse rental costs and their broader implications for market dynamics, investment decisions, and policy frameworks. Design/methodology/approach: A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, analyzing peer-reviewed studies (2014–2025) from databases such as Scopus, Web of Science, and ScienceDirect. The determinants were categorized into location factors, market conditions, services, and physical attributes. Findings/Result: Key drivers of rental costs include proximity to transport hubs, economic trends, supply-demand fluctuations, and regulatory policies. In addition, warehouse automation and green-building certifications are emerging as new pricing factors. Conclusion: Warehouse rental pricing is shaped by a complex interplay of economic, geographic, and technological factors. Understanding these trends enables businesses, investors, and policymakers to optimize logistics strategies and site selection. Originality/value (state of the art): This study bridges research gaps by offering a holistic framework that integrates economic, spatial, and technological determinants, providing actionable insights for logistics and real estate stakeholders. Keywords: warehouse rent, supply chain, logistics real estate, economic determinants, market trends, sustainability